Teachers' Perspective On Guidance and Counseling Best Practices in Islamic Early Childhood Education - Esya Anesty Mashudi; Fatihaturosyidah Fatihaturosyidah; Yuli Nurmalasari (Jurnal PG-PAUD, 2023)
Guidance and counseling services primarily aim to anticipate any potential misbehavior at the Early Childhood Education (ECE) level. Hence, it is necessary to design a comprehensive model of guidance and counseling which is philosophically, contextually, empirically, and culturally suit Indonesian system of formal education. The present study served as one of basic research which is attempted to depict early childhood teachers and educators’ perspectives on the implementation of guidance and counseling services in Raudhatul Athfal (RA) and Islamic Kindergarten (IK). To this end, a descriptive exploratory method was applied by involving early childhood educators from six RA and IK in Serang City. The data were collected using an open ended questionnaire, observation, interview, and study documentation and analyzed using the interactive analysis model consisting of three stages: data display, data reduction, and generalization. The findings indicated that, in general, although participants in this study considered guidance and counseling services important for preschool children, they had not understood the mechanism in implementing the services and the individual who should provide the services. Following the findings, a perceived ideal guidance and counseling model that suitable for the Islamic early childhood education is the model which is based on Islamic values derived from Al Quran and Sunnah of the Prophet.